2019
DOI: 10.1177/1753193418819653
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral scapholunate widening may have a nontraumatic aetiology and progress to carpal instability and osteoarthritis with advancing age

Abstract: It was hypothesized that bilateral widening of the scapholunate gap is relatively common in the absence of trauma and that it progresses to radiological carpal instability and scapholunate advanced collapse. Electronic files of 1000 patients with bilateral X-rays were studied in retrospect. Wide scapholunate gaps were bilaterally present in 67 and unilaterally in 51 patients. Scapholunate advanced collapse was observed in 26 patients; in nine it was in both wrists. A trauma was recorded in less than half of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Even if SLIL degeneration grading was lower in these subjects, we suppose that dorsal ganglion cysts could be one of the first imaging signs of midcarpal instability due to structural abnormalities of SLIL, in the same manner as meniscal cysts of the knee are associated to meniscal tears ( 27 ) . As arthrographic studies demonstrated that wrist compartments are often well separated, so the finding of dorsal ganglion cyst immediately over a slightly degenerated SLIL should alert the clinician to possible wrist instability due to SLIL pathology ( 4 , 28 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if SLIL degeneration grading was lower in these subjects, we suppose that dorsal ganglion cysts could be one of the first imaging signs of midcarpal instability due to structural abnormalities of SLIL, in the same manner as meniscal cysts of the knee are associated to meniscal tears ( 27 ) . As arthrographic studies demonstrated that wrist compartments are often well separated, so the finding of dorsal ganglion cyst immediately over a slightly degenerated SLIL should alert the clinician to possible wrist instability due to SLIL pathology ( 4 , 28 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic injuries or progressive degenerative changes of SLIL can lead to internal derangement of carpal bones ( 3 , 4 ) , instability of midcarpal joints (often associated to production of synovial ganglion cysts), and eventually to scapholunate advanced collapse (SLAC), which is the most common cause of osteoarthritis involving the wrist ( 5 ) . Both calcium pyrophosphate dihydrates (CPPD) crystal deposition disease (CPDD) arthropathy and rheumatoid arthritis (RA) are rheumatologic conditions associated with wrist instability and SLAC ( 6 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Those causes are more commonly observed in patients with bilateral wrist changes. 28,[34][35][36] analyzed radiographs from both wrists of 1,000 people with no recent trauma, and found 67 of those cases of bilateral and 51 of unilateral SL space widening. 34 There were signs of SLAC in 26 wrists, and, of those, 9 were bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…(continued) ,10,38,40,43,49,57,58,66,76,89,101,104,107,111,127,128,[132][133][134]137,146,167,171,172,174,181,182,195,46,48,51,70,71,74,85,95,113,121,124,125,163,173,176,177,180,183,[187][188][189][190][191]201,202 Sex unclear or not reported5-7,9,10,34,38,40,45,50-52,54,55,63,65,67,68,71,73,76,80,81,83,84,88-90,96,98,99,101-103,106,109-111,113, …”
mentioning
confidence: 99%